2008
DOI: 10.1111/j.1600-0501.2008.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of mandibular reconstruction with autogenous bone grafts and oral implants after tumor resection

Abstract: Results from this study demonstrated that bone defects following resection of mandibular tumors can be predictably reconstructed with autogenous bone grafts taken from the calvarium or the anterior iliac crest. It has also been shown that the long-term survival and success rates of implants placed in the reconstructed areas (96.7% and 93.3%, respectively) may guarantee an excellent prognosis of implant-supported prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 17 publications
5
95
0
3
Order By: Relevance
“…Iliac crest can be recommended in almost all reconstructive situations because it reinforces the resistance of the maxilla, re�establishes its continuity improving facial contour, and provides adequate height and width of bone. Once the graft has consolidated, these reconstructions have proved to be very acceptable aesthetically and functionally to support dental prostheses or for the insertion of dental implants (5,9). However, iliac crest bone grafts present the major problem of its unpredictable resorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iliac crest can be recommended in almost all reconstructive situations because it reinforces the resistance of the maxilla, re�establishes its continuity improving facial contour, and provides adequate height and width of bone. Once the graft has consolidated, these reconstructions have proved to be very acceptable aesthetically and functionally to support dental prostheses or for the insertion of dental implants (5,9). However, iliac crest bone grafts present the major problem of its unpredictable resorption.…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem occurs in the maxilla if the graft keeps in contact and communication with natural cavities, as the resorption of the graft may be higher due to compromised re�vascularization and exposition to possible infection. Many publications in the last few years have reported very good results with the use of implants and implant�supported prostheses in reconstructed patients after tumor resection, and demonstrated that they seem to reduce bone resorption significantly, probably due to the fact that prosthetic load stimulates the graft and inhibits bone resorption (5,10). The period of time of delay between bone graft reconstruction and implant placement can fluctuate from 4 to 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 It also provides adequate bone for the reconstruction of the maxillofacial defects and facial contour, otherwise it is possible to place implants with acceptable resorption rates due to long term results in the literature. 4,16 Chiapasco et al 4 compared behavior of the implants in bone grafts which were placed after reconstruction of the resected mandibles. They found similar peri-implant bone resorption in autogenous grafts (anterior iliac crest or fibula) and revascularized iliac or fibula flaps, 24 months after prosthetic load.…”
mentioning
confidence: 99%
“…If bone loss is significant, intraoral facial prosthetics are the only realistic option for recovering the facial profile and some degree of oral function, such as speaking, mastication and swallowing. Autogenous bone is the gold-standard material for such reconstruction because it has a high inherent physiological capacity for bone formation and demonstrates similar mechanical properties to those of the excised bone [1][2][3][4][5][6][7] , but also carries the risk of extensive bone resorption at the donor site 6) . A heterograft may be used as an alternative, but is itself complicated by the possibility of cross-infection 8,9) .…”
Section: Introductionmentioning
confidence: 99%